Practical guide to prevention of contrast‐induced acute kidney injury after percutaneous coronary intervention. Issue 3 (22nd January 2020) - Bugani, Giulia; Ponticelli, Francesco; Giannini, Francesco; Gallo, Francesco; Gaudenzi, Eleonora; Laricchia, Alessandra; Fisicaro, Andrea; Cimaglia, Paolo; Mangieri, Antonio; Gardi, Ilja; Colombo, Antonio
Abstract: Contrast‐induced acute kidney injury (CI‐AKI) represents a common but serious complication of percutaneous coronary interventions (PCI)—and in general of all those examinations requiring iodinated contrast injection—which affects not only renal function but also long‐term prognosis. While several prophylactic approaches were designed in order to prevent CI‐AKI, most failed to demonstrate clear benefits in randomized trials, and their implementation is therefore discouraged in clinical practice. The most notorious examples include pre‐procedural bicarbonate or N‐acetylcysteine, and preprocedural withdrawal of ACE inhibitors/Angiotensin receptor blockers. Those strategies that were instead demonstrated effective include the appropriate use of preprocedural hydration, reduction in contrast volume utilization, adoption of techniques for zero‐ or ultra‐low‐contrast procedures, and pharmacological treatments with statins. In this brief review, we summarize the main preventive strategies into brief and pragmatic recommendations designed to improve everyday clinical practice.